2012
DOI: 10.1155/2012/675805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Progenitor Cells during Canine Retinal Development

Abstract: We identify the presence of progenitor cells during retinal development in the dog, as this species represents a natural model for studying several breed-specific degenerative retinal disorders. Antibodies to detected progenitor cells (Pax6, C-kit, and nestin) and ganglion cells (BDNF, Brn3a, and Thy1) were used in combination with H3 for the purpose of identifying proliferating cells. Pax6, nestin, C-kit, and H3 were localized mainly in the neuroblastic layer of the retina during the embryonic stage. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…HLA-DR expression was very low in both fvERM and primary hRPE cells, while no HLA-G expression was detected on these cells that is in line with previous findings [2730]. Animal studies have shown that CD117/c-kit is more likely expressed by retinal progenitor cells [3133] and angiogenic cells [18, 34], which to a certain extent was the case with our primary hRPE, but not the fvERM cells. From the fibroblastoid or mesenchymal stem cell (MSC) markers (CD73, CD90, and CD105) [35], CD73 was present on both fvERM and primary hRPE cells.…”
Section: Discussionsupporting
confidence: 88%
“…HLA-DR expression was very low in both fvERM and primary hRPE cells, while no HLA-G expression was detected on these cells that is in line with previous findings [2730]. Animal studies have shown that CD117/c-kit is more likely expressed by retinal progenitor cells [3133] and angiogenic cells [18, 34], which to a certain extent was the case with our primary hRPE, but not the fvERM cells. From the fibroblastoid or mesenchymal stem cell (MSC) markers (CD73, CD90, and CD105) [35], CD73 was present on both fvERM and primary hRPE cells.…”
Section: Discussionsupporting
confidence: 88%
“…1-3) and BDNF (Figs. [4][5][6] immunolabeling patterns were similar, with labeling being either locally extensive or diffuse. The intensity of immunolabeling varied from weak to strong within the same tumor.…”
Section: Prongf and Bdnf Expressionmentioning
confidence: 85%
“…The tyrosine kinase receptor c-kit is activated by its ligand stem cell factor and acts as the primary growth factor for mast cells. It is also expressed in a range of other cell types including melanocytes, mammary cells, Purkinje cells, interstitial cells of Cajal, neuroblastic cells of the retina, Leydig cells and spermatogonia, mature dendritic cells and most (but not all) haematopoietic stem cells (Rico-Vargas et al 1994, Huss et al 1995, Reguera et al 2000, Morini et al 2004, Gilfillan & Rivera 2009, Usher et al 2009, Grieco et al 2010, Avila-Garcia et al 2012, Lennartsson & Ronnstrand 2012.…”
Section: Choosing Medical Therapy For Mct Based On the Presence Of C-kit Mutationmentioning
confidence: 99%